3D-Cultured Vascular-Like Networks Enable Validation of Vascular Disruption Properties of Drugs In Vitro - Yavvari, Prabhusrinivas; Laporte, Anna; Elomaa, Laura; Schraufstetter, Fabian; Pacharzina, Inga; Daberkow, Aline Dominique; Hoppensack, Anke; Weinhart, Marie (Frontiers in Bioengineering and Biotechnology, 2022)
Vascular disrupting agents are an interesting class of anti-cancer compounds because of their combined mode of action in preventing new blood vessel formation and disruption of already existing vasculature in the immediate microenvironment of solid tumors. The validation of vascular disruption properties of these drugs in vitro is rarely addressed due to the lack of proper in vitro angiogenesis models comprising mature and long-lived vascular-like networks. We herein report an indirect coculture model of human umbilical vein endothelial cells (HUVECs) and human dermal fibroblasts (HDFs) to form three dimensionally profuse vascular-like networks. HUVECs embedded and sandwiched in the collagen scaffold were cocultured with HDFs located outside the scaffold. The indirect coculture approach with vascular endothelial growth factor (VEGF) producing HDFs triggered the formation of progressively maturing lumenized vascular-like networks of endothelial cells within less than seven days, which have proven to be viably maintained in culture beyond day 21. Molecular weight dependent Texas red-dextran permeability studies indicated high vascular barrier function of the generated networks. Their longevity allowed us to study the dose-dependent response upon treatment with the three known anti-angiogenic and/or vascular disrupting agents brivanib, combretastatin-A4-phosphate (CA4P) and 6´-sialylgalactose (SG) via semi-quantitative brightfield and qualitative confocal laser scanning microscopic (CLSM) image analysis. Compared to reported data on the in vivo efficacy of these drugs in terms of anti-angiogenic and vascular disrupting effects we observed similar trends with our 3D model which are not reflected in conventional in vitro angiogenesis assays. High vascular disruption under continuous treatment of the matured vascular-like network was observed at concentrations ≥ 3.5 ng·mL-1 for CA4P and ≥ 300 nM for brivanib. In contrast, SG failed to induce any significant vascular disruption in vitro. This advanced model of a 3D vascular-like network allows for testing single and combinational anti-angiogenic and vascular disrupting effects with optimized dosing and may thus bridge the gap between in vitro and in vivo experiments in validating hits from high-throughput screening. Moreover, the physiological 3D environment mimicking in vitro assay is not only highly relevant to in vivo studies linked to cancer but also to the field of tissue regeneration.